Studi Keragaman Mesofauna Tanah Pada Beberapa Vegetasi Di Kawasan Taman Nasional Kelimutu - Fendra Suarmadi; Sri Wahyuni; Willybrordus Lanamana (Agriculture Faculty of Flores University, 2011)
The goal of this research was to understand the diversity of soil mesofauna native to different plant habitats in the area of Kelimutu National Park and to understand how the dominant soil mesofaunal populations vary depending on vegetative diversity. This research was conducted in a number of different vegetation habitat zones according to the intensity of land use in the area of Kelimutu National Park and in the laboratories at the University of Flores in the city of Ende. This research was designed in a linear method and sampled vegetation from areas labelled VR (Vacciniumvaringiaefoliumdan Rhododendron renschiamum), VCa (mixed forest) and VC (coniferous forest). The results of this research show that the area near Kelimutu National Park contains low to medium diversity. Low diversity was observed in areas with vegetation VR with5 types of soil mesofauna (H’:1.153) whereas medium diversity was observed in areas with vegetation VCa, with researchers finding 7 types of soil mesofauna (H’:1.771). Six types of soil mesofauna were found in areas with vegetation type VC (H’:1.727). Vegetative diversity was found to be linked to the increasing dominance of soil mesofauna in the area of Kelimutu National Park. The highest value of vegetative diversity was (H’:1.821), found in area VCa with the dominance of soil mesofauna (E:0,85). For area VR, the vegetative diversity was (H’:1,771) with a dominant soil mesofauna value of (E:0.72) and for vegetation VC the vegetative diversity was (H’:0.861) with dominant soil mesofauna value of (E: 0,28).